Pandemic shocks and time-varying weak-form efficiency in ASEAN foreign exchange markets: An empirical investigation - Saizal Pinjaman; Sook Ching Kok; Sarma Aralas; Agus Tri Basuki; Syamsul Hadi; Pazri Nugraha; Susilo Nur Aji Cokro Darsono (Optimum: Jurnal Ekonomi dan Pembangunan, 2026)
This study examines the weak-form Efficient Market Hypothesis (EMH) for the selected ASEAN exchange rates—Brunei Darussalam, Indonesia, the Philippines, Singapore, and Thailand—relative to the U.S. dollar (USD) over three distinct phases: pre-COVID-19 (2010–2019), during COVID-19 (2020–2021), and post-COVID-19 (2022–2023). Using monthly nominal exchange-rate data from the World Bank and applying the Augmented Dickey–Fuller (ADF) unit root test, the study evaluates whether these exchange rates exhibit random-walk behavior consistent with weak-form efficiency. The results reveal that all ASEAN currencies were I(1) and efficient before the pandemic, supporting the weak-form EMH. However, efficiency deteriorated during COVID-19, particularly for Malaysia and Singapore, where exchange rates became stationary at level, indicating short-term predictability due to policy interventions and market disruptions. In the post-pandemic period, Malaysia and Singapore regained efficiency, while Indonesia and Thailand exhibited partial mean-reverting tendencies, reflecting gradual market normalization. Descriptive statistics further confirm increased volatility during the pandemic and partial stabilization thereafter. Overall, the findings suggest that ASEAN exchange-rate efficiency is time-varying, resilient under stable conditions but vulnerable during systemic shocks. Policy recommendations include enhancing monetary transparency, promoting flexible exchange-rate management, and strengthening regional financial coordination to sustain efficiency during future crises.